2018
DOI: 10.3390/molecules23102473
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Gelatin/β-Cyclodextrin Composite Fiber Adsorbents for the Efficient Removal of Dyes from Wastewater

Abstract: In this paper, environmentally friendly gelatin/β-cyclodextrin (β-CD) composite fiber adsorbents prepared by electrospinning were used for the removal of dyes from wastewater. Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and a universal materials tester were employed to characterize the internal structures, surface morphologies and mechanical strength of the composite fiber adsorbents. Additionally, the fiber was evaluated as an adsorbent for the removal of methylene blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…As shown in Figure 6a, the spectra of GZ1 and GZ2 represent three characteristic peaks at 1629, 1531 and 1236 cm −1 corresponding to amide I, amide II and amide III, respectively. The amide I band is mainly attributed to the tensile vibration of -C=O, and the amide II and III bands are caused by the bending vibration of -NH and the stretching vibration of -C-N, respectively [34]. A weak absorption peak at 407 cm −1 in the GZ1 and GZ2 spectra is consistent with the characteristic absorption peak of ZnO (as mentioned in Section 3.1.1), which belongs to the stretching vibration of the Zn-O bond.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6a, the spectra of GZ1 and GZ2 represent three characteristic peaks at 1629, 1531 and 1236 cm −1 corresponding to amide I, amide II and amide III, respectively. The amide I band is mainly attributed to the tensile vibration of -C=O, and the amide II and III bands are caused by the bending vibration of -NH and the stretching vibration of -C-N, respectively [34]. A weak absorption peak at 407 cm −1 in the GZ1 and GZ2 spectra is consistent with the characteristic absorption peak of ZnO (as mentioned in Section 3.1.1), which belongs to the stretching vibration of the Zn-O bond.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the pseudo first-order model and pseudo second-order model were used to characterize the adsorption kinetics toward Ni(II), as expressed as follows [ 34 , 35 ]:…”
Section: Resultsmentioning
confidence: 99%
“…A new peak appeared at 420 cm −1 in the case of the fibers containing ZnO/GO corresponding to the stretching vibration peak of the Zn-O bond (Figure 6b), and an extra peak at 668 cm −1 could be assigned to the metal-oxygen stretching mode [16], which represents that ZnO/GO have been incorporated in the gelatin fibers successfully. The characteristic peaks of amid I, amid II and amid III observed at 1637, 1540 and 1244 cm −1 , respectively, both in GELF and ZGF were mainly attributed to -C=O stretching, -NH stretching and -C-N stretching, respectively [27]. In addition, the characteristic peak at 1454 cm −1 was mainly attributed to the stretching vibration peak of the imide group (-CH=N), which was caused by the reaction between the aldehyde group of formaldehyde and the amino lysine residue of gelatin [29].…”
Section: Characterization Of Zno/go-gelatin Fibersmentioning
confidence: 94%
“…The result indicated that different from uncross-linked gelatin fibers, which dissolve in aqueous solutions instantly, GEL and ZGF could be degraded completely in 7 days. Chen et al used the steam of formaldehyde/ethanol solution to crosslink the gelatin membranes, which was basically degraded after 5 days [27]. Eldin et al added glutaraldehyde into gelatin and chitosan mixture to crosslink the membranes; the weight loss of the crosslinked membranes was about 42% after 6 days [28].…”
Section: Characterization Of Zno/go-gelatin Fibersmentioning
confidence: 99%